Hechos y valores en psicooncología - Barbero, Javier (Psicooncología, 2003)
The psycho oncologist knows that his technical decisions have an ethical component, though only it is because "to know" generates "power"; of there the necessary mediation of the "duty". To be a professional of excellence the psycho oncologist has to handle thoroughly the clinical aspects, the therapeutic communication and the moral analysis, having to be this one sufficiently well based on rational criteria and with analytical and deliberative solidly founded methodology. There are not facts without values and in psychooncology some facts turn into challenge from the ethical perspective: the decision taking process, the team work, the role of autonomy of the patient, the dialectics between reason and feeling, the experience of fragility and the obligations of responsibility, the link between the therapeutic communication and the moral deliberation and – above all - the moral imperative of response that supposes the experience of suffering of the patient of cancer and his family. The moral category of a society measures up for its capacity in offering alternatives to their more fragile and helplessness members; in this respect, the presence of psychooncologists in the Services of Oncology and / or Palliative Care turns, in west, in a question of justice, that not of beneficence; this is based not only for the effectiveness of his offers, but also for his efficiency.